Decentralization of Nursing Care: The Chilean National Health Service and the Professionalization of Nursing 1950-1970 [Os Desafios Da Descentralização Da Assistência de Enfermagem: O Serviço Nacional de Saúde Do Chile E a Profissionalização Da Enfermagem 1950-1970] [Los Desafíos de la Descentralización de Los Cuidados de Enfermería: El Servicio Nacional de Salud Chileno y la Profesionalización de la Enfermería 1950-1970] - Navarro-Torres, R; Nunez-Carrasco, E; Macias-Inzunza, L (Universidad de Alicante, 2021)
The article aims to analyze the challenges of the decentralization of nursing care in the historical period from 1950 to 1970. Method: A historical analysis of the professionalization of the nurse and the National Health Service was carried out from its initial phases until 1970 The secondary documentary sources are magazines of the College of Nurses of Chile, reports, unpublished documents and Bulletins of the National Service, the primary sources are life stories of nurses who worked at the end of the decade of the 50s. Results: The following categories, the challenges of the establishment of the National Health Service, lights and shadows of the professionalization of nursing. Conclusions: The National Health Service granted a health structure under the responsibility of the Chilean State for the health of all its inhabitants from Arica to Punta Arenas. In this scenario, professional nurses were recognized by the health authority, granting them structure and decision-making in health. Likewise, the very organization of the National Service allowed progress in the decentralization of care. © 2021 Universidad de Alicante. All rights reserved.
Keywords: History of nursing, nurse; public health; national health service; Chile